(untitled) - Gogola, Marian (Doprava a spoje, 2007)
This contribution deals with transport-social survey results which ran in Zilina county. The results provided the useful information about the inhabitants travel habits which were applied in process of public transport modelling. Generally a survey is possible to use in public transport demand determination, evaluation and analysis transport trend, public transport quality, sustainable mobility etc. These advantages designate the survey to be a powerful tool in travel demand forecasting